A high temperature resistant high thermal conductivity ultra-wideband composite microwave absorbing coating and preparation method thereof

By combining epoxy resin, MXene sheet powder and carbonyl iron powder, a high-temperature resistance high-thermal conductivity ultra-wideband composite wave absorbing coating is formed, which solves the problems of narrow absorption bandwidth and poor high-temperature resistance of existing composite wave absorbing coatings, and achieves ultra-wideband absorption performance and excellent high-temperature resistance and high-thermal conductivity.

CN119144211BActive Publication Date: 2025-03-25UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411600447.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-25
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing composite wave absorbing coatings have problems such as narrow absorption bandwidth, poor overall absorption efficiency, poor environmental adaptability and poor high temperature resistance.

Method used

Epoxy resin is used as the binder, and composite single-layer MXene sheet powder and carbonyl iron powder form a high-temperature-resistant high-thermal conductivity ultra-wideband composite wave absorbing coating, achieving the ultra-wideband absorption performance of the wave absorbing coating and excellent high-temperature and high thermal conductivity.

Benefits of technology

The ultra-wideband absorption performance of the absorbing coating is achieved, and the reflection loss of less than -10 dB in the frequency bands of 70~110 GHz and 0.3~1.2 THz is achieved, and the absorption performance is maintained in a high-temperature environment, with excellent high temperature resistance and high thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144211B_ABST
    Figure CN119144211B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electromagnetic absorption materials, and relates to high-performance electromagnetic absorption materials in the millimeter wave band and the terahertz wave band. Specifically, a high-temperature resistant, high-thermal-conductivity, ultra-wideband composite absorbing coating and a preparation method thereof are provided to solve the problems of narrow absorption bandwidth, poor overall absorption efficiency, poor environmental adaptability, and poor high-temperature resistance of existing composite absorbing coatings. In the present invention, the composite absorbing coating is composed of epoxy resin (EP), Ti 3 C 2 T x (MXene) and carbonyl iron powder (CIP), based on the epoxy resin component content of 40g, the carbonyl iron powder component content is 10g~40g, the Ti 3 C 2 T x The component content is 2g~6g. In summary, the present invention uses epoxy resin as a binder, and composites a single-layer MXene flaky powder and carbonyl iron powder to form a composite absorbing coating, which achieves ultra-wideband absorption performance of the absorbing coating and has excellent high temperature resistance and high thermal conductivity; and the composite absorbing coating has a simple preparation process and low preparation cost, which is conducive to industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electromagnetic absorption materials, and relates to high-performance electromagnetic absorption materials in millimeter wave bands and terahertz wave bands, and specifically provides a high-temperature resistant, high-thermal-conductivity, ultra-wideband composite absorbing coating and a preparation method thereof. Background Art

[0002] With the rapid development of wireless communication technology and intelligent electronic devices, various digital and high-frequency electronic and electrical equipment have brought great convenience to human life, but the problem of electromagnetic radiation pollution has become increasingly serious. Electromagnetic absorption materials can convert incident electromagnetic waves into heat or other forms of energy for dissipation, thereby reducing the harm of electromagnetic radiation. It is conceivable that future communications and electronic devices will be multi-band integration from high-frequency millimeter waves to terahertz waves. Electromagnetic radiation (EMI) absorption, especially electromagnetic radiation absorption that takes into account both millimeter wave and terahertz bands, will become increasingly important. Therefore, it is urgent to develop high-performance electromagnetic absorption materials (EAMs) covering millimeter wave bands and terahertz bands to eliminate electromagnetic radiation leakage and create a safe electromagnetic environment. In particular, in radiation detection devices and quasi-optical systems, high-performance electromagnetic absorption materials can ensure the normal operation of precision electronic integrated devices.

[0003] To date, most reported electromagnetic absorption materials from GHz to THz have focused on metamaterial arrays and patterned two-dimensional (2D) materials; however, due to the relatively narrow-band absorption characteristics of the material itself, resonant units of different sizes from centimeters to microns must be integrated to obtain broadband electromagnetic absorption properties. High-precision graphic design, complex preparation processes and large thicknesses have limited the large-scale manufacturing and practical application of these electromagnetic absorption devices.

[0004] Ti3C2T xAs a new type of two-dimensional carbon / nitrogen compound, MXene has important research value in electromagnetic wave absorption and shielding. On the one hand, MXene has a unique two-dimensional layered structure, and the interlayer spacing can be expanded by other means to achieve multiple reflections and scattering. On the other hand, the high conductivity of MXene makes it have strong dielectric loss. Some surface defects and functional groups will be generated during the etching process, and dipoles will be generated under the action of the electromagnetic field, which will enhance the electromagnetic loss capacity of the material. However, the high conductivity of MXene will lead to poor impedance matching. In order to improve the attenuation capacity of MXene for electromagnetic waves, MXene is often compounded with other materials to form a composite absorbing material to improve the absorbing performance, such as a MXene-based absorbing material, preparation method and application disclosed in the patent document with publication number CN116769326A. At the same time, polymer-based composite materials have attracted wide attention due to their excellent mechanical properties, chemical stability and heat resistance. Among various polymers doped with absorbents, epoxy resin (EP for short) has attracted much attention due to its excellent mechanical properties and adhesion. First, due to the presence of large active oxygen-containing groups and hydroxyl functional groups in the molecular structure of EP, its activity is strong and it is easy to react with other groups. Second, EP has stable performance and corrosion resistance. Third, since EP can be dissolved in most organic solvents when not solidified, it can be sealed for a long time at room temperature. Fourth, EP has good processing performance and can be mixed with other materials in any proportion. At present, EP and its composite materials are widely used in coatings, electrical appliances, construction and other application fields. However, the existing composite absorbing coatings have the problems of narrow absorption bandwidth and poor overall absorption efficiency, and the composite absorbing coatings have poor environmental adaptability and poor high temperature resistance. Based on this, the present invention uses epoxy resin as a binder to provide a high temperature resistant, high thermal conductivity, ultra-wideband composite absorbing coating and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to provide a high-temperature resistant, high-thermal-conductivity, ultra-wideband composite absorbing coating and a preparation method thereof, so as to solve the problems of narrow absorption bandwidth, poor overall absorption efficiency, poor environmental adaptability, and poor high-temperature resistance of existing composite absorbing coatings. The present invention uses epoxy resin (EP for short) as a binder, and composites a single-layer MXene flaky powder and carbonyl iron powder (CIP) to form a composite absorbing coating, thereby achieving ultra-wideband absorption performance of the absorbing coating, and having excellent high-temperature resistance and high thermal conductivity.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A high temperature resistant, high thermal conductivity, ultra-wideband composite absorbing coating, characterized in that the composite absorbing coating is composed of epoxy resin (EP), Ti3C2T x(MXene) and carbonyl iron powder (CIP), with the content of the epoxy resin being 40g as the benchmark, the content of the carbonyl iron powder being 10g~40g, and the Ti3C2T x The component content is 2g~6g.

[0008] Furthermore, the preparation method of the above-mentioned high temperature resistant high thermal conductivity ultra-wideband composite absorbing coating is characterized by comprising the following steps:

[0009] Step 1: Ti3C2T x Synthesis of dispersions;

[0010] A mixture of hydrofluoric acid (HF) and hydrochloric acid (HCl) was used to selectively etch Ti3AlC2 to synthesize a single layer of Ti3C2T x Dispersion liquid;

[0011] Step 2, preparation of MXene flake powder;

[0012] For single-layer Ti3C2T x The dispersion is centrifuged, and the obtained precipitate is condensed and dried, and the precipitate after condensation and drying is ground into a micron-sized single-layer MXene flake powder;

[0013] Step 3, preparation of composite radar absorbing coating;

[0014] A single layer of MXene flake powder and carbonyl iron powder (CIP) are added to epoxy resin (EP) in proportion, and the mixture is stirred and mixed to obtain a high temperature resistant, high thermal conductivity, ultra-wideband composite absorbing coating.

[0015] Furthermore, the specific process of step 1 is:

[0016] First, 2 mL HF, 12 mL HCl, and 6 mL deionized water were mixed in a plastic bottle;

[0017] Then, 1 g of Ti3AlC2 powder was added to the mixed solution, and a water bath magnetic stirrer was used to stir at 450-500 rpm / min for 24 h at 35°C for etching; after etching, the solution was poured into a centrifuge tube and centrifuged at 8000 rpm / min for 5-10 min, and then the solution was repeatedly washed with deionized water until pH > 6; then, the precipitate was mixed with 1 g of LiCl and 50 mL of deionized water, and intercalated with a water bath magnetic stirrer at 400-450 rpm / min for 4-5 h at 35°C; after intercalation, a centrifuge was used to centrifuge at 8000 rpm / min for 20-30 min, and the mixture was washed with deionized water for 10-15 min until the precipitate swelled;

[0018] Finally, the swollen precipitate was dispersed in deionized water and then centrifuged at 3500 rpm / min for 5-10 min to obtain a uniformly dispersed monolayer Ti3C2T x Dispersion.

[0019] Furthermore, the specific process of step 2 is:

[0020] First, a single layer of Ti3C2T x The dispersion was poured into a centrifuge tube and centrifuged at 8000 rpm / min for 10-15 min. The supernatant was then poured out, leaving the monolayer Ti3C2T x Sediment;

[0021] Then, the precipitate was placed in a condensation dryer, the cold trap temperature was set to -80 °C, the vacuum pressure was set to 0.01 Pa, and freeze-dried for 24 h;

[0022] Finally, the dried precipitate was poured out and ground into single-layer MXene nanosheet powder using a ball mill.

[0023] Furthermore, the specific process of step 3 is:

[0024] First, weigh the epoxy resin adhesive and add it into a beaker, and stir it mechanically at a speed of 400-600 r / min for 10-15 min in a 35°C water bath.

[0025] Then, carbonyl iron powder (CIP) and single-layer MXene nanosheet powder were weighed in proportion, added to the epoxy resin binder, and mechanically stirred at a speed of 400-600 r / min for 20-30 min;

[0026] Finally, the beaker was placed in a vacuum dryer and vacuum dried at 50°C for 1-2 h to remove bubbles, thereby obtaining a high-temperature resistant, high-thermal-conductivity, ultra-wideband composite absorbing coating.

[0027] Furthermore, the application of the above-mentioned high temperature resistant high thermal conductivity ultra-wideband composite absorbing coating is characterized in that an epoxy resin curing agent is added to the high temperature resistant high thermal conductivity ultra-wideband composite absorbing coating at a ratio of 20:1, mechanically stirred at 200-300r / min for 3-5 min, and then poured into a flat mold; the mold is placed on a heating table and cured at 65°C for 2-3 h. After curing, the mold is taken out and cooled, and demolding is performed to obtain a high temperature resistant high thermal conductivity ultra-wideband composite absorbing flat plate.

[0028] Furthermore, the thickness of the composite absorbing plate is 1-2 mm.

[0029] Based on the above technical solution, the beneficial effects of the present invention are:

[0030] 1) The present invention designs an ultra-wideband composite absorbing coating with high temperature resistance and high thermal conductivity. Compared with the prior art, the present invention realizes the ultra-wideband absorption performance of the absorbing coating, which can achieve a reflection loss of less than -10 dB in the frequency range of 70~110 GHz and 0.3~1.2 THz;

[0031] 2) The present invention designs a high-temperature resistant, high-thermal-conductivity ultra-wideband composite absorbing coating, which has excellent high-temperature resistance and high thermal conductivity and can maintain its absorbing performance in a high-temperature environment;

[0032] 3) The present invention designs a method for preparing a high-temperature resistant, high-thermal-conductivity ultra-wideband composite absorbing coating, which has a simple preparation process and low preparation cost and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a process flow chart for preparing a single-layer Mxene in the present invention.

[0034] Figure 2 The present invention is a process flow chart for preparing the high temperature resistant high thermal conductivity ultra-wideband composite microwave absorbing coating.

[0035] Figure 3 These are scanning electron microscope (SEM) images of the monolayer MXene powder and carbonyl iron powder in the present invention, wherein (a) is the monolayer MXene powder and (b) is the carbonyl iron powder.

[0036] Figure 4 The cross-sectional scanning electron microscope (SEM) images of the composite absorbing plate of the present invention are shown in FIG. 1 , wherein (a) is 100 μm and (b) is 50 μm.

[0037] Figure 5 This is a physical picture of the composite absorbing flat plate in the present invention.

[0038] Figure 6 It is a curve diagram of reflection loss variation of the composite absorbing coating in the present invention within the frequency range of 75 to 110 GHz.

[0039] Figure 7 The graph is a reflection loss variation curve of the composite absorbing coating in the present invention within the frequency range of 0.3-1.2 THz.

[0040] Figure 8 This is a thermogravimetric analysis curve of the composite absorbing coating of the present invention.

[0041] Fig. 9 The graph is a curve showing the change in reflection loss of the composite absorbing coating of the present invention with temperature in the frequency range of 75 to 110 GHz.

[0042] Fig.10 The graph is a curve showing the reflection loss of the composite absorbing coating of the present invention changing with temperature in the frequency range of 0.3-1.2 THz.

[0043] Fig.11 It is a thermal conductivity curve diagram of the composite absorbing coating in the present invention. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and beneficial effects of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0045] The present invention provides a high-temperature resistant, high-thermal-conductivity, ultra-wideband composite absorbing coating, which realizes the ultra-wideband absorption performance of the absorbing coating and has excellent high-temperature resistance and high thermal conductivity. The composite absorbing coating is composed of epoxy resin (EP), Ti3C2T x (MXene) and carbonyl iron powder (CIP), with the content of the epoxy resin being 40g as the benchmark, the content of the carbonyl iron powder being 10g~40g, and the Ti3C2T x The component content is 2g~6g.

[0046] For the above-mentioned high temperature resistant high thermal conductivity ultra-wideband composite absorbing coating, the present invention provides Examples 1 to 9. At the same time, the present invention also provides Comparative Example 1. The composition ratio of the composite absorbing coating in Examples 1 to 9 and Comparative Example 1 is shown in Table 1.

[0047] Table 1

[0048]

[0049] The composite radar absorbing coatings in Examples 1 to 9 and Comparative Example 1 are prepared by the following steps:

[0050] Step 1: Ti3C2T x Synthesis of dispersions, such as Figure 1 As shown;

[0051] First, 2 mL HF, 12 mL HCl, and 6 mL deionized water were mixed in a plastic bottle;

[0052] Then, 1 g of Ti3AlC2 powder was slowly added to the solution, and a water bath magnetic stirrer was used to stir at 500 rpm / min for 24 h at 35°C for etching; after etching, the solution was poured into a centrifuge tube and centrifuged at 8000 rpm / min for 8 min, and the solution was repeatedly washed with deionized water and tested with pH paper until pH > 6; then, the obtained precipitate was mixed with 1 g LiCl and 50 mL deionized water, poured into a plastic bottle, added with a long magnetic strip, and stirred at 400 rpm / min for 4 hours at 35°C using a water bath magnetic stirrer for intercalation; after intercalation, a centrifuge was used to centrifuge at 8000 rpm / min for 30 min, and the mixture was washed with deionized water for 10 min until the precipitate swelled;

[0053] Finally, the swollen precipitate was dispersed in deionized water and then centrifuged at 3500 rpm / min for 5 min to obtain uniformly dispersed Ti3C2T x Dispersion liquid;

[0054] Step 2, preparation of MXene flake powder;

[0055] First, Ti3C2T x The dispersion was poured into a centrifuge tube and centrifuged at 8000 rpm / min for 10 min. The supernatant was then poured out, leaving a single layer of Ti3C2T x Sediment;

[0056] Then, the precipitate was placed in a condensation dryer, the cold trap temperature was set to -80 °C, the vacuum pressure was set to 0.01 Pa, and freeze-dried for 24 h;

[0057] Finally, the dried precipitate was poured out and ground with a ball mill to obtain a single-layer MXene nanosheet powder;

[0058] Step 3: Preparation of composite absorbing coating, such as Figure 2 As shown;

[0059] First, the epoxy resin adhesive was weighed and added into a beaker, and then mechanically stirred at 500 r / min for 10 min in a 35°C water bath.

[0060] Then, carbonyl iron powder and monolayer MXene nanosheet powder were weighed and added into epoxy resin binder, and mechanically stirred at 500 r / min for 30 min;

[0061] Finally, the beaker was placed in a vacuum dryer and vacuum dried at 50° C. for 1 h to remove bubbles therein, thereby obtaining a composite radar-absorbing coating.

[0062] Furthermore, in the Examples 1 to 9 and Comparative Example 1, in order to test the performance of the prepared composite absorbing coating, the composite absorbing coating was processed into a composite absorbing flat plate for testing; the preparation process of the composite absorbing flat plate is as follows:

[0063] First, 2 g of epoxy resin curing agent was added to the prepared composite absorbing coating, and mechanically stirred at a speed of 200 r / min for 3 min;

[0064] Then, prepare a flat plate mold, spray a release agent on its inner surface, and then pour the absorbing coating into the flat plate mold for packaging;

[0065] Finally, the mold was placed on a heating table and cured at 65°C for 2 h. After curing, the flat plate mold was taken out and cooled, and the composite absorbing flat plate was demoulded to obtain the composite absorbing flat plate.

[0066] The excellent performance of the high temperature resistant, high thermal conductivity, ultra-wideband composite absorbing coating provided by the present invention is described in detail below in combination with the working principle and test results.

[0067] In terms of working principle:

[0068] For absorbing materials, achieving broadband strong absorption generally requires the following conditions to be met at the same time: good impedance matching characteristics and strong intrinsic loss; first, in order to achieve the minimum direct surface reflection, it is necessary to ensure that the electromagnetic wave can enter the absorbing material as much as possible. According to the principle of electromagnetic wave propagation, the input impedance of the material surface can be derived. The expression of the direct reflection coefficient R is as follows:

[0069]

[0070] in, represents the free space impedance, ; represents the vacuum permeability, ; represents the vacuum dielectric constant, Therefore, to minimize the reflection of electromagnetic waves, it is necessary to ensure and To maximize the matching; for electromagnetic waves incident vertically on the surface of the absorbing material, the reflection loss (RL) can be calculated by transmission line theory, which is obtained by the following formula:

[0071]

[0072]

[0073] in, represents the relative magnetic permeability of the material, represents the relative dielectric constant of the material, represents an imaginary number ( × =-1), represents the incident frequency of electromagnetic waves, d represents the thickness of the absorbing material, and c=3×10 8 m / s represents the propagation speed of light in a vacuum. It can be seen from the formula that the reflection of electromagnetic waves at the surface of the material is closely related to the impedance of the material surface. At the same time, the reflection loss RL is also affected by the dielectric constant and magnetic permeability of the material. When the metal material is used as the substrate, the reflection loss equation of the absorbing material can be expressed as:

[0074]

[0075] The absorbing material itself absorbs radar waves. The basic types include absorbers with basically equal complex magnetic permeability and complex dielectric constant, "broadband" absorbers with gradient impedance, and thin-layer absorbers with attenuated surface current. When the electromagnetic wave enters the absorbing material, the electric field propagation equation is as follows:

[0076]

[0077] Where z represents the propagation distance, represents the propagation phase, Represents the attenuation constant (referring to the ability of electromagnetic waves to enter the material and be consumed inside the material); generally speaking, in order to obtain excellent wave absorption performance, the basic factor that must be considered is the electromagnetic wave attenuation ability of the absorbing material; the electromagnetic attenuation ability is usually characterized by the attenuation coefficient (α), and the specific formula is as follows:

[0078]

[0079] in, and Represent the real and imaginary parts of the relative dielectric constant of the absorbing material, and represent the real and imaginary parts of the relative magnetic permeability of the absorbing material respectively; therefore, The larger the absorbing material, the better its absorption performance, and the material needs to have a larger relative dielectric constant and magnetic permeability; but due to the higher operating frequency, the displacement polarization and natural resonance of the dielectric or magnetic medium cannot keep up with the response changes of the electromagnetic wave frequency, making it difficult for the absorbing material that originally relied on dielectric loss or magnetic loss to achieve efficient absorbing performance;

[0080] In addition, the interference dissipation of the absorbing material is another key factor in attenuating electromagnetic waves, which can be described by a quarter-wavelength matching mechanism. When the thickness of the absorbing material is exactly equal to an odd multiple of a quarter wavelength of the electromagnetic wave, the phase of the reflected wave on the surface of the absorbing material is exactly 180° different. According to the derivation, for interference destructiveness to occur, the relationship between the thickness d of the absorbing material and the frequency f of the incident electromagnetic wave can be expressed as:

[0081]

[0082] in, is a positive integer; therefore, the frequency of interference destructive phase determines the frequency range of the reflection loss peak. When designing absorbing materials in different frequency bands, the values ​​of relative magnetic permeability and relative dielectric constant can be reasonably selected according to this formula to select suitable absorbing materials; however, in the traditional sense, microwave absorbing materials that usually have a single loss mechanism mainly based on dielectric loss or magnetic loss are difficult to have the function of absorbing losses in the terahertz frequency band; therefore, the purpose of the present invention is to obtain a material with high-frequency broadband absorbing performance with the smallest possible thickness.

[0083] Since MXene has a unique two-dimensional layered structure and its interlayer spacing can be expanded by other means, it can achieve multiple reflections and scattering, so that the incident electromagnetic wave is fully attenuated; the high conductivity of MXene makes it have strong dielectric loss, and some surface defects and functional groups will be generated during the etching process. They will produce dipoles under the action of the electromagnetic field, which will increase the electromagnetic loss capacity of the material; however, the high conductivity of MXene will make the interface reflection high and the impedance matching poor, which will increase the reflection loss. In order to improve the attenuation capacity of MXene for electromagnetic waves, the present invention mixes MXene with the magnetic loss material carbonyl iron powder, so that the interface generated by the combination of the microsphere structured carbonyl iron powder and the nanosheet-shaped MXene is The increase in the number of surfaces is beneficial to enhancing the interface polarization effect. In addition, the natural resonance and eddy current loss after the addition of carbonyl iron powder provide an effect on the magnetic loss, thereby further optimizing the impedance matching characteristics and improving the electromagnetic wave attenuation capability, thereby expanding the effective absorption bandwidth of the absorbing coating. In order to improve the absorbing performance and high temperature resistance of the composite absorbing coating, the present invention uses epoxy resin as a binder. Due to the presence of large active oxygen-containing groups and hydroxyl functional groups in the molecular structure of epoxy resin, it has strong activity and can react with the polar functional groups in MXene to produce strong dipole polarization, thereby increasing the attenuation capability of electromagnetic waves. Moreover, epoxy resin is resistant to corrosion and high temperature, has stable performance, and can improve the overall high temperature resistance of the composite absorbing coating.

[0084] From the test results:

[0085] Taking the composite absorbing coatings prepared in Examples 1 to 3 as examples, the beneficial effects of the present invention are described in detail in combination with Comparative Example 1;

[0086] like Figure 3 The figure shows the scanning electron microscope images of the single-layer MXene powder and the carbonyl iron powder. It can be seen from the figure that the single-layer MXene prepared by the present invention has a flaky structure, and the carbonyl iron powder agglomerates to form a spherical structure; Figure 4 The cross-sectional SEM image of the absorbing plate pressed by the composite absorbing coating is shown. It can be seen from the figure that the flake MXene and the spherical carbonyl iron powder are evenly dispersed in the epoxy resin; Figure 5 The picture shows the actual composite absorbing plate, which is only 1.5 mm thick;

[0087] like Figure 6 The figure shows the reflection loss variation curve of the composite absorbing coating in the frequency range of 75~110 GHz, wherein the carbonyl iron powder is simplified as CIP, the single-layer MXene nanosheet powder is simplified as MX, and the line CIP20-MX0 represents the comparative example 1, and the lines CIP20-MX2, CIP20-MX4, and CIP20-MX6 represent the embodiments 1 to 3 respectively; it can be seen from the figure that compared with the comparative example 1, the absorbing performance of the composite absorbing coating provided by the present invention is significantly improved, especially the absorbing effect of the embodiment 2 in the whole frequency band is the best, and the reflection loss is below -10 dB; as shown in FIG. Figure 7 The figure shows the reflection loss variation curve of the composite absorbing coating in the frequency range of 0.3~1.2THz. Similarly, the reflection loss of Example 2 in the entire frequency range is also lower than -10 dB, and most of it is below -15 dB, which proves that the composite absorbing coating also has good absorbing performance in the terahertz frequency band and has ultra-wideband absorption performance.

[0088] like Figure 8 The thermogravimetric analysis curve of the composite absorbing coating of Example 2 (CIP20-MX4) is shown to indicate the thermal stability of the composite absorbing coating, wherein carbonyl iron powder is simplified as CIP, single-layer MXene nanosheet powder is simplified as MX, epoxy resin is simplified as EP, and line CIP20-MX4 represents Example 2; it can be seen from the figure that within the air temperature range of room temperature to 600°C, the composite absorbing coating obtains thermal stability that meets the mass loss ratio; in more detail, the temperature at which the mass loss of the composite material is 10% can be defined as the decomposition temperature, recorded as Td, and the composite absorbing material in Example 2 remains thermally stable at a high temperature of 400°C; as shown in FIG. Fig. 9 FIG. 2 is a graph showing the change in reflection loss of the composite absorbing coating of Example 2 with temperature in the frequency range of 75 to 110 GHz. Fig.10The figure shows the curve of reflection loss of the composite absorbing coating of Example 2 in the frequency range of 0.3~1.2 THz as a function of temperature. It can be seen from the figure that the composite absorbing material after heating has similar reflection loss curves in the frequency range of 75~110 GHz and 0.3~1.2 THz, and the reflection loss in the total frequency range is still below -10 dB, that is, the composite absorbing material can maintain the absorption performance before heating after high temperature treatment at 300°C, proving that the absorbing coating of the present invention has excellent high temperature resistance.

[0089] like Fig.11 The figure shows the thermal conductivity of the composite absorbing coating at 150°C, wherein the carbonyl iron powder is simplified as CIP, and the single-layer MXene nanosheet powder is simplified as MX. The abscissa CIP0-MX0 represents pure epoxy resin, the abscissa CIP20-MX0 represents comparative example 1, and the abscissas CIP20-MX2, CIP20-MX4, and CIP20-MX6 represent embodiments 1 to 3, respectively. As can be seen from the figure, the thermal conductivity of the epoxy resin is 1.28 W / (m⋅K), and the thermal conductivity of the composite absorbing material in comparative example 1 and embodiments 1 to 3 is 1.56 W / (m·K), 1.81 W / (m·K), 2.082 W / (m·K), and 2.17 W / (m·K), respectively. The results show that since CIP and MXene can effectively establish a thermal conductive path when filled in the epoxy resin matrix as fillers, thereby synergistically enhancing its thermal conductivity, the composite absorbing material has high thermal conductivity characteristics.

[0090] In summary, the present invention provides a high temperature resistant, high thermal conductivity, ultra-wideband composite absorbing coating, which realizes the ultra-wideband absorption performance of the absorbing coating and has excellent high temperature resistance and high thermal conductivity.

[0091] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A high temperature resistant, high thermal conductivity, ultra-wideband composite microwave absorbing coating, characterized in that: The composite absorbing coating is composed of epoxy resin, single-layer MXene flaky powder and carbonyl iron powder. The content of the epoxy resin component is 40g, the content of the carbonyl iron powder component is 10g-40g, and the content of the single-layer MXene flaky powder component is 2g-6g. The carbonyl iron powder adopts a microsphere structured carbonyl iron powder, and the single-layer MXene flaky powder adopts a single-layer nano-flaky Ti3C2T x .

2. The method for preparing the high temperature resistant high thermal conductivity ultra-wideband composite microwave absorbing coating according to claim 1, characterized in that: The following steps are involved: Step 1: Ti3C2T x Synthesis of dispersions; Ti3AlC2 was selectively etched using a mixture of hydrofluoric acid and hydrochloric acid to synthesize a single layer of Ti3C2T x Dispersion liquid; Step 2, preparation of MXene flake powder; For single-layer Ti3C2T x The dispersion is centrifuged, and the obtained precipitate is condensed and dried, and the precipitate after condensation and drying is ground into a micron-sized single-layer MXene flake powder; Step 3, preparation of composite radar absorbing coating; A single layer of MXene flake powder and carbonyl iron powder are added to epoxy resin in proportion, and stirred and mixed to obtain a high temperature resistant, high thermal conductivity, ultra-wideband composite absorbing coating.

3. The method for preparing the high temperature resistant high thermal conductivity ultra-wideband composite microwave absorbing coating according to claim 2, characterized in that: The specific process of step 1 is: First, 2 mL HF, 12 mL HCl, and 6 mL deionized water were mixed in a plastic bottle; Then, 1 g of Ti3AlC2 powder was added to the mixed solution and etched using a water bath magnetic stirrer at 35 °C at a speed of 450-500 rpm / min for 24 h; After etching, the solution was poured into a centrifuge tube and centrifuged at 8000 rpm / min for 5-10 min, and then the solution was repeatedly washed with deionized water until pH > 6; then, the precipitate was mixed with 1 g LiCl and 50 mL deionized water, and stirred at 400-450 rpm / min for 4-5 hours at 35 °C using a water bath magnetic stirrer for intercalation; after the intercalation was completed, the solution was centrifuged at 8000 rpm / min for 20-30 min, and the mixture was washed with deionized water for 10-15 min until the precipitate swelled; Finally, the swollen precipitate was dispersed in deionized water and then centrifuged at 3500 rpm / min for 5-10 min to obtain a uniformly dispersed monolayer Ti3C2T x Dispersion.

4. The method for preparing the high temperature resistant high thermal conductivity ultra-wideband composite microwave absorbing coating according to claim 2, characterized in that: The specific process of step 2 is: First, a single layer of Ti3C2T x The dispersion was poured into a centrifuge tube and centrifuged at 8000 rpm / min for 10-15 min. The supernatant was then poured out, leaving a single layer of Ti3C2T x Sediment; Then, the precipitate was placed in a condensation dryer, the cold trap temperature was set to -80 °C, the vacuum pressure was set to 0.01 Pa, and freeze-dried for 24 h; Finally, the dried precipitate was poured out and ground into single-layer MXene nanosheet powder using a ball mill.

5. The method for preparing the high temperature resistant high thermal conductivity ultra-wideband composite microwave absorbing coating according to claim 2, characterized in that: The specific process of step 3 is: First, weigh the epoxy resin adhesive into a beaker and stir it mechanically at 400-600 rpm / min for 10-15 min in a 35°C water bath. Then, carbonyl iron powder and single-layer MXene nanosheet powder were weighed in proportion, added to the epoxy resin binder, and mechanically stirred at a speed of 400-600 r / min for 20-30 min; Finally, the beaker was placed in a vacuum dryer and vacuum dried at 50°C for 1-2 h to remove bubbles, thereby obtaining a high-temperature resistant, high-thermal-conductivity, ultra-wideband composite absorbing coating.

Citation Information

Patent Citations

  • MXene-based wave-absorbing material, preparation method and application

    CN116769326A

  • Broadband high-absorption material based on sparse large-particle magnetoelectric cooperation mechanism

    CN118725508A